2016
DOI: 10.12659/msm.898110
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-152 Targets Phosphatase and Tensin Homolog to Inhibit Apoptosis and Promote Cell Migration of Nasopharyngeal Carcinoma Cells

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is a type of head and neck cancer with very high prevalence in southern China. Phosphatase and tensin homolog (PTEN), a tumor suppressor, was reported to be downregulated in NPC patients and correlated with pathological grade and clinical stage of NPC.Material/MethodsLuciferase reporter assay, qPCR, and Western blot analysis were used to determine if PTEN is a target of miR-152. The function of miR-152 in cell apoptosis and cell proliferation was examined as well. Tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…miR-152, a member of miR-148/152 family, has been reported to be downregulated, and to function as a tumor suppressive miRNA in majority types of cancer (11)(12)(13)(14)(15)(16). In contrast, in neuroblastoma and nasopharyngeal carcinoma, miR-152 expression was upregulated, suggesting that miR-152 acts as an oncogene miRNA (21,22). These results suggested that miR-152 could serve as either oncogene or tumor suppressor in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…miR-152, a member of miR-148/152 family, has been reported to be downregulated, and to function as a tumor suppressive miRNA in majority types of cancer (11)(12)(13)(14)(15)(16). In contrast, in neuroblastoma and nasopharyngeal carcinoma, miR-152 expression was upregulated, suggesting that miR-152 acts as an oncogene miRNA (21,22). These results suggested that miR-152 could serve as either oncogene or tumor suppressor in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the suppression of miR-152 biogenesis increases cisplatin resistance in epithelial ovarian cancer (55). However, the overexpression of miR-152 increases cisplatin resistance and proliferation of nasopharyngeal carcinoma cells (56), while the overexpression of miR-762 stimulates the development of various tumors, including ovarian (57) and breast cancer (58). Conversely, the expression of miR-762 (in combination with other miRNAs) leads to the apoptosis of breast cancer cells (59).…”
Section: Discussionmentioning
confidence: 99%
“…The present study assessed the potential mechanism by which increased miR-152 levels modulates the malignant progression of cervical cancer. It has been suggested that the phosphatase and tensin homolog (PTEN), a tumor suppressor, is decreased in patients with nasopharyngeal carcinoma (NPC) and is associated with the pathological grade and clinical stage of NPC (36). It has been demonstrated that the reduced expression of PTEN in patients with NPC may be associated with the upregulation of miR-152, thereby inhibiting cell apoptosis and enhancing cancer cell proliferation and migration during NPC development (36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the phosphatase and tensin homolog (PTEN), a tumor suppressor, is decreased in patients with nasopharyngeal carcinoma (NPC) and is associated with the pathological grade and clinical stage of NPC (36). It has been demonstrated that the reduced expression of PTEN in patients with NPC may be associated with the upregulation of miR-152, thereby inhibiting cell apoptosis and enhancing cancer cell proliferation and migration during NPC development (36). Similarly, the results of the present study indicated that increased miR-152 levels are identified in patients with CIN and patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%